Statistical Damage Shear Constitutive Model of Rock Joints Under Seepage Pressure - Xie, Shijie; Lin, Hang; Chen, Yifan; Wang, Yixian; Cao, Rihong; Li, Jiangteng (Frontiers in Earth Science, 2020)
The constitutive relation of rock joints in the percolation environment has always been a frontier research topic in the field of geotechnical engineering, involving nuclear waste disposal, dam foundation construction, tunnel tunneling, and other fields. In this study, a shear statistical damage constitutive model of rock joints considering seepage pressure was proposed, which takes into account the statistical damage, stage deformation characteristics and seepage action in the process of joint shear deformation. By introducing the seepage pressure reduction coefficient and establishing the relationship between the model parameters and the seepage pressure, the prediction of joint shear stress-displacement curves under different seepage pressures was achieved. The comprehensive comparisons between the theoretical results and the experimental results reveals that the model can accurately reflect the shear deformation law of joints and reasonably simulate the shear stress-displacement relationship of joints. And ultimately, the physical significance of the model parameters and their relationship with shear strength characteristics are discussed via the gray correlation method. The model and verification results presented in this study can deepen the understanding of the shear behavior of joints subject to high seepage pressure and contribute to the design and optimization of geotechnical engineering in the percolation environment.